PENGARUH PENGGUNAAN INFORMASI AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJER PADA PERUSAHAAN KONTRAKTOR DI KOTA MANADO. - Tumbel, Natalia Gladys; Karamoy, Herman; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Competition increased business today requires companies to enhance existing capabilities as much as possible , in order to excel in competition . To survive in today's competitive business environment , businesses must be able to create conditions that are flexible and innovative business , and businesses need to consider external factors are more difficult to predict . Competitive advantage can be created by the company can be achieved one way , which improves performance because the company is required manajer.Oleh umtuk has advantages over other companies . Manager of the company 's performance is one of the success or failure response company goals . The purpose of this study was to determine the effect of the use of management accounting information to managers on the performance of contractor in the city of Manado . Objects that are examined in this study are contracting companies in the city of Manado the number of samples studied were 30 respondents . The independent variable ( X ) are examined in this study is the management accounting information as well as the dependent variable ( Y ) is the manager 's performance . This study uses a simple linear regression analysis and obtained the equation Y = 13 914 + 0.291 X Results calculated determination coefficient of 0.175 gives the sense that the manager of the company 's performance is affected by factors accounting information management results of this study indicate that management accounting information significantly affect the performance of managers in Contractor companies in the city of Manado.